Abundance of Bacteria in Municipal Supply Water of Kushtia Town, Bangladesh: A Case Study (Bangladesh Journal of Genetics and Biotechnology, 2009)
Bangladesh j. genet. biotechnol. 7 (1&2): 105-106, 2006 (June & December)